Answer: x = 0, and y = -2
Explanation:
-5x + y = -2 .........(1)
-3x + 6y = -12 ......(2)
From equation (1)
-5x +y = -2 .........(1)
y = 5x - 2 .............(3)
Now substitute for y in equation (2)
-3x + 6 (5x -2 ) = -12
Make use of 6 to open the bracket ,we now have
-3x + 30x - 12 = -12
= 27x - 12 = -12
Collect the like terms
27x = -12 + 12
27x = 0
Divide through by 27 to get the value of x
x = 0/27
x = 0
To determine y, substitute for x in equation (3)
y = 5x - 2
y = 5(0) - 2
y = 0 - 2
y = -2
Check : Substitute for x and y in equation (1)
-5x + y = -2
-5(0) + (-2) = -2
0 -2 = -2
0 - 2 = -2